MORPHOFUNCTIONAL CHANGES IN THE LIVER OF 24-MONTH-OLD RATS IN THE EARLY STAGES OF EXPERIMENTAL DIABETES MELLITUS DEVELOPMENT - Zhurakivska, O.Ya.; Bodnarchuk, Yu.V.; Pertsovych, V.M.; Kulynych, H.B.; Мiesoiedova, V.A. (World of Medicine and Biology, 2018)
The purpose of the research work was to establish the peculiarities of morphofunctional changes in the liver in the early stages of streptozotocin-induced diabetes mellitus (DM). Diabetes mellitus was induced by a single intraperitoneal injection of streptozotocin (5mg per 100g of body weight). Specimens for the study were collected on the 14th and 28th day of the experiment. Histologic, electron-microscopic, and biochemical methods of investigation were used. The study revealed that in streptozotocin-induced diabetes mellitus with the increase of levels of glucose and glycosylated hemoglobin the granular degeneration of hepatocytes with the transition to vacuolar degeneration takes place. Structural changes in the liver lead to its dysfunction, which is confirmed by the increased levels of specific hepatic aminotransferases and the decreased De Ritis ratio starting from the 14th day of the experiment. Such changes are followed by the increased activity of pro-oxidant system which is confirmed by the significant increase of levels of superoxide dismutase in blood serum and liver homogenates.
Keywords: liver; liver transaminase; superoxide dismutase; streptozotocin-induced diabetes mellitus